Involvement of Hsp90 and cyclophilins in intoxication by AIP56, a metalloprotease toxin from Photobacterium damselae subsp. piscicida - Rodrigues, IS (2019)
AIP56 (apoptosis inducing protein of 56 kDa) is a key virulence factor secreted by virulent strains of Photobacterium damselae subsp. piscicida (Phdp), a Gram-negative bacterium that causes septicemic infections in several warm water marine fish species. AIP56 is systemically disseminated during infection and induces massive apoptosis of host macrophages and neutrophils, playing a decisive role in the disease outcome. AIP56 is a single-chain AB-type toxin, being composed by a metalloprotease A domain located at the N-terminal region connected to a C-terminal B domain, required for internalization of the toxin into susceptible cells. After binding to a still unidentified surface receptor, AIP56 is internalised through clathrin-mediated endocytosis, reaches early endosomes and translocates into the cytosol through a mechanism requiring endosomal acidification and involving low pH-induced unfolding of the toxin. At the cytosol, the catalytic domain of AIP56 cleaves NF-¿B p65, leading to the apoptotic death of the intoxicated cells. It has been reported that host cytosolic factors, including host cell chaperones such as heat shock protein 90 (Hsp90) and peptidyl-prolyl cis/trans isomerases (PPIases), namely cyclophilin A/D (Cyp) and FK506-binding proteins (FKBP) are involved in the uptake of several bacterial AB toxins with ADP-ribosylating activity, but are dispensable for the uptake of other AB toxins with different enzymatic activities, such as Bacillus anthracis lethal toxin (a metalloprotease) or the large glycosylating toxins A and B of Clostridium difficile. Based on these findings, it has been proposed that the requirement for Hsp90/PPIases is a common and specific characteristic of ADP-ribosylating toxins. In the present work, we demonstrate that Hsp90 and the PPIases cyclophilin A/D are required for efficient intoxication by the metalloprotease toxin AIP56. We further show that those host cell factors interact with AIP56 in vitro and that the interactions increase when AIP56 is unfolded. The interaction with Hsp90 was also demonstrated in intact cells, at 30 min post-treatment with AIP56, suggesting that it occurs during or shortly after translocation of the toxin from endosomes into the cytosol. Based on these findings, we propose that the participation of Hsp90 and Cyp in bacterial toxin entry may be more disseminated than initially expected, and may include toxins with different catalytic activities.